Post-caesarean Rectus Sheath Haematoma - Upadhyaya, I; Joshi, NR (Nepal Journal of Obstetrics and Gynaecology, 2016)
Rectus sheath haematoma of the abdomen is the accumulation of blood in the sheath of the rectus abdominis muscle as a result of disruption of the epigastric vessels or from a direct tear of the muscle itself. The aberrant course of vessels or injudicious dissection may contribute to this catastrophe. It encompasses a wide spectrum of severity - some self-limiting and others fatal depending on its size, etiology and the development of complications. Its common features include acute abdominal pain, fever, nausea and vomiting. The non-specific nature of these symptoms combined with the low incidence of the disorder lead to difficulty in diagnosis. Local trauma, coagulopathies, coughing, hypertension, and peripheral vascular disease could cause them. The haematoma usually occurs in the lower quadrants of the abdominal wall, is difficult to diagnose clinically and often radiologic imaging is required for its definitive pre-operative diagnosis. Our patients presented with rectus sheath haematoma, following caesarean section. Clinical suspicion and ultrasonography were used to confirm the diagnosis and patients were managed with exploration and haematoma drainage.